2018
DOI: 10.1002/jclp.22730
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mediating role of self‐blame and coping in the relationships between self‐compassion and distress in females following the sexual assault

Abstract: Objective: The present study investigated the associations between self-compassion, self-blame, disengagement coping, and posttraumatic stress disorder (PTSD) and depression symptom severity among females who had experienced sexual assault. We also examined whether the relationships between self-compassion and both PTSD and depression severity were mediated by self-blame and coping. Method: A volunteer sample of female adults (N = 207)completed surveys online or on paper.Results: Mediational analyses showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 52 publications
5
30
1
Order By: Relevance
“…Ten of the papers employed mediational analysis to explore the relationships between self‐compassion, trauma, and PTSD. One study found a significant direct relationship between self‐compassion and PTSD (Bistricky et al, ), and four studies found indirect relationships via interpersonal competence (Bistricky et al, ), emotional dysregulation (Barlow et al, ), self‐blame attributions, and disengagement coping (Hamrick & Owens, ) and grief ruminations (Lenferink et al, ). Scoglio et al () reversed the constructs and found that emotion regulation also mediated the relationship between PTSD and self‐compassion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten of the papers employed mediational analysis to explore the relationships between self‐compassion, trauma, and PTSD. One study found a significant direct relationship between self‐compassion and PTSD (Bistricky et al, ), and four studies found indirect relationships via interpersonal competence (Bistricky et al, ), emotional dysregulation (Barlow et al, ), self‐blame attributions, and disengagement coping (Hamrick & Owens, ) and grief ruminations (Lenferink et al, ). Scoglio et al () reversed the constructs and found that emotion regulation also mediated the relationship between PTSD and self‐compassion.…”
Section: Resultsmentioning
confidence: 99%
“…Maheux and Price () found no difference in ratings of self‐compassion by trauma type or by exposure to multiple types of traumatic events; however, they noted that participants who met criteria for PTSD reported lower levels of self‐compassion (Maheux & Price, ). One study utilizing a nonclinical sample of female survivors of sexual assault found that participants with a history of CSA showed no significant difference in level of self‐compassion compared with those with no history of CSA (Hamrick & Owens, ). No strong patterns emerged across trauma types; however, notable, physical abuse was not related self‐compassion in two studies (Miron et al, ; Wu et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher self-compassion was related to lower experiential avoidance and anger rumination, similar to findings for trait-mindfulness. In the relationship between racial microaggressions and self-blame and rumination, it was found that higher self-compassion was related to higher self-blame and rumination, respectively; both of these findings are inconsistent with previous research (Hamrick & Owens, 2018;Svendsen, Kvernenes, Wiker, & Dundas, 2017).…”
Section: Self-compassioncontrasting
confidence: 71%